(untitled) (European Journal of Marketing and Economics, 2023)
Considering Malaysia as a multi-ethnic country, it is difficult to determine and define the cultural identity to represent Malaysia (Mun, Fern, & Chin, 2015), and use it as a characteristic in designing a product. This has been a challenging issue for most Malaysian local designers to design a Malaysia-look product based on a national identity characteristic. There is no proof that the product characteristic can be summed up or generalized based on the understanding of multi-ethnic agreement decision-making (Zainal, Othman, & Samsudin, 2015). With regards to Malaysia, the primary issue is about the national identity identification for product design. This issue then prompted to the question that would Malaysian designers be able to establish a Malaysian product with a national identity by looking at this multi-ethnic society? This research reviews the literature concerning Malaysian identity based on articles and visuals. It aims at getting the general keywords related to the components in culture and yet to be incorporated with the design characteristics at the beginning of ideation process. The basis of this study is referring to the dominant culture study by Edensor (2002), cultural identity components evaluation by Ibrahim (2015), and culture and identity ‘key issues’ by Clarke (2011). By understanding the cultural component within the society, pulling out the keywords, and validating the chosen keywords by conducting a survey, these keywords will act as the guidance in visualising a characteristic; and there will be greater chances for Malaysian designer to success in developing products with strong Malaysian identities.